Discovery of Small Molecule Inhibitors Targeting the Sonic Hedgehog - Yun, Taikangxiang; Wang, Juan; Yang, Jun; Huang, Wenjing; Lai, Luhua; Tan, Wenfu; Liu, Ying (Frontiers in Chemistry, 2020)
The aberrant activation of hedgehog (Hh) signaling pathway is closely related to human diseases. The upstream protein, N-terminal product of sonic hedgehog (ShhN) is overexpressed in many cancers and considered as a promising antitumor target. Inhibitors that bind to ShhN and break its interaction with the 12-transmembrane glycoprotein patched (Ptch) protein are highly wanted to tune down the abnormal Hh pathway activation. However, research of ShhN inhibitors remains lacking. In this paper, we computationally screened potential inhibitors against the ShhN-Ptch interaction interface, and tested their activities preliminary by experimental studies. Seven compounds (1-7) with diverse scaffolds, showed inhibition in cellular assays and directly bound to ShhN in vitro. The compounds were verified to modulate the Hh pathway activity. Furthermore, we studied the structure-activity relationship of the pyrimidine (7) derivatives and identified a potent compound (7_3d3) with IC50 of 0.4 ±0.1μM in cellular assays. These small molecule inhibitors of ShhN provide novel chemical probes for future investigations of Hh signaling.